Effectiveness of arbuscular mycorrhizal fungi native from Agave rhizosphere as growth promoters in papaya - Quiñones Aguilar, Evangelina Esmeralda; Hernández Cuevas, Laura Verónica; López Pérez, Luis; Rincón Enríquez, Gabriel (REVISTA TERRA LATINOAMERICANA, 2019)
Arbuscular mycorrhizal fungi (AMF) are benef icial symbionts of most terrestrial plants. This symbiosis brings benef its to both symbionts. The plant involved in the symbiosis is supplied with nutrients by the fungus that promotes plant growth, in exchange for energy for reproduction of the AMF. In this context, the effectiveness of multi-specif ic AMF inocula from the rhizosphere of Agave cupreata from Michoacán, Mexico, in promoting the growth of papaya plants was evaluated. An experiment was carried out in ten random blocks with eleven treatments: eight consortiums of AMF, a commercial biofertilizer based on AMF (EndoMic®), a reference strain (Claroideoglomus claroideum) and a control without AMF. One hundred days after establishing the experiment, we evaluated the variables plant height, stem diameter, dry biomass of foliage, root and total, foliar area, relative index of mycorrhizal dependence, mycorrhizal colonization and density of mycorrhizal spores. The data were analyzed through an analysis of variance and correlation. The results showed that two of the consortiums promoted plant growth eff iciently; the plants inoculated with the consortiums AD-MTu and CM-MT signif icantly increased (Tukey, P ≤ 0.05) dry biomass by 240 and 225%, respectively, relative to the control without AMF, while with the biofertilizer EndoMic® the increase for the same variable was only 12%. It is concluded that the use of consortiums of AMF promotes the growth of papaya and therefore could be used in nurseries or greenhouses.